Evaluasi Rencana Strategi (Renstra) Periode Tahun 2013-2017 Pada Dinas Pemuda dan Olahraga Provinsi DKI Jakarta Menggunakan Metode Rapid Assessment Procedures (RAP) - Silfia Silfia (Peneliti.net, 2023)
The Strategic Plan Document (Renstra) is guided by the Regional Medium Term Development Plan (RPJMD), the Regional Long Term Development Plan (RPJPD) and by taking into account the National Medium Term Development Plan (RPJM). The purpose of this study is to conduct a strategic planning evaluation contained in the Strategic Plan (RENSTRA) of the DKI Jakarta Provincial Youth and Sports Service Office 2013-2017 using Rapid Assessment Procedures (RAP) method. The evaluation includes two evaluation stages, namely, the first stage is to evaluate synchronization between strategic planning documents. In this evaluation the evaluation method used is the Rapid Assessment Evaluation model. The second stage is an evaluation to measure the achievement of organizational performance. Gap Analysis evaluation model is to determine the comparison of actual performance with potential or expected performance. The results of the evaluation using the Rapid Assessment method, synchronization between the strategy documents that exist in the DKI Jakarta Provincial Youth and Sports Service for the 2013-2017 period have been realized, the percentage of documents from 2013-2017 is each criteria of the total policy (Objectives, Goals , Programs, Activities and Indicators) which should be explained still <10%. The results of performance measurement at the DKI Jakarta Provincial Youth and Sports Service for the 2013-2017 period on 5 (five) targets have been determined as many as 11 (eleven) performance indicators can be concluded that: 4 (four) performance indicators or 36.36% are categorized beyond the target, 2 (two) performance indicators or 18.18% with categories according to target, 4 (four) performance indicators or 36.36% categorized as not achieving the target, 1 (one) performance indicator is not available data